Early Identification of Mpox Clinical Features and Its Significance for Epidemic Control - WU Yu, SHANG Weijing, LIU Min, LIANG Wannian (Zhongguo quanke yixue)
Recently, a new sub-branch Ⅰb of Mpox virus (MPXV) has triggered a new round of Mpox outbreak. 2024-08-14, Mpox was once again classified as a public health emergency of international concern (PHEIC) by the WHO. Early detection and diagnosis of Mpox cases is the key to interrupting the spread of Mpox in hospitals. In this article, we will review the pathogenetic features, epidemiological features, clinical features, diagnostic criteria, preventive and control measures of Mpox, with a view to providing reference for the early identification, scientific prevention and control of Mpox.